O sistema Ficus Adathodifolia Schott (Moraceae) – Tetrapus sp. (Chalcidoidea – Agaonidae): desenvolvimento do sicônio e histologia da galha floral - Priscilla Pacheco (2016)
The mutualistic pollinating relationship in figs (Ficus spp.) was established throughout a series of adjustments between the syconiua and their pollinating wasps (Hymenoptera, Chalcidoidea, Agaonidae), which take place in the floral ovary. In Ficus spp.-Agaonidae systems, the plants offer part of their reproductive structures as a reward to their pollinators namely, sites for oviposition and sites for larva nutrition. Floral galls of Ficus spp. are induced by wasps oviposition between the integument and the nucellus. A single larva develops and feeds in the endosperm, with evidences that the process of gall formation may be independent of fertilization. The model of current study is the Ficus adhatodifolia-Tetrapus system, to which the phenology of the syconium and the morphological changes during the formation of floral galls were evaluated. Fig production and all developmental stages were observed all over the year, with higher fruiting rates in warmer and humid periods. The fig has a floral receptacle with round apex, bounded by ostiolar bracts. These bracts expand in fig maturation, for the emergence of adult female wasps. The receptacle wall presents essentially parenchymatic cells, it is highly vascularized, with interspersed sclereids in maturation phase. The ostiolar bracts and the outer cell layers of the syconium wall produce volatiles to attract pollinating wasps. Inside the fig, the style length is a limiting factor to oviposition, in a way that long-styled flowers should never form galls. Gall tissues are derived from the flower and ovule tissues, keeping characteristics of the pollinated flower.